Applied supervised learning with Python : use scikit-learn to build predictive models from real-world datasets and prepare yourself for the future of machine learning /: use scikit-learn to build predictive models from real-world datasets and prepare yourself for the future of machine learning. (2019) - Johnston, Benjamin; Mathur, Ishita
No abstract available